Applying Organizational Ambidexterity in strategic management under a “VUCA” environment: Evidence from high tech companies in China - Jingjing Du; Zhongwei Chen (International Journal of Innovation Studies, 2018)
High tech organizations confront dual demands of exploration and exploitation, particularly in today’ s competitive environment marked by a trend of volatility, uncertainty, complexity, and ambiguity. Although there is general consensus about the relationship between ambidexterity and firm performance, few studies have probed into the mechanism of how it is applied in the strategic management process. Considering the premise of environmental change, this research considers a multilevel perspective on the nature of organizational ambidexterity and its functioning in the whole strategic management process. Through a comparative case study of the two most famous high tech companies in China, a model is provided to reflect the functioning of organizational ambidexterity where a cognitive pattern of top management teamsplays a critical role in the ability that the organizations demonstrate. This research also contributes to the literature of entrepreneurship by extending innovation from a demand-side perspective, where the core of product/market exploration/exploitation activities could be expanded into customer value creation. Undertaking a careful analysis of the mechanism of organizational ambidexterity, this research sheds new light on the literature of strategic management that operates in a more turbulent environment. Keywords: Organizational ambidexterity, Exploration, Exploitation, Strategic management